Secure Data Transfer in Personal Area Network - Kumar, Shiv; shrama, Shrawan kumar; kumar, Awanit (IJRDO -Journal of Computer Science Engineering, 2015)
Now a d’ays everyone using net in their home or in small office or we can say within a smallarea. The problem is transfer data from one node to other node in a room or in a hall with minimum costingand minimum maintenance. But we have to save energy also. There are several techniques or method totransfer data in a small premise like Wi-Fi, Bluetooth, Li-Fi and quantum physics. According to ourrequirement security means privacy, integrity, timeliness and non repudiation. While costing is mostimportant for small organization also. Implementation and maintenance of Wi-Fi is more costly then Li-Fi.Li-Fi is more secure then Wi-Fi because data is transfer from one node to another is done using light. It iscost effective also because we have not to use additional light to light the room or office. Its maintenance isalso very easy. So, we can say that LI-Fi is better than Wi-Fi in terms of costing, privacy and maintenance.